Effect of Diaphragm Breathing Exercise on Reducing Anxiety Level of Pregnant Women - Rosyati Pastuty; eliza dora; siti hindun (Poltekkes Kemenkes Palembang, 2021)
Background: Anxiety is one of the emotional disorders in pregnant women that commonly occurs in the third trimester. As many as 28.7% of anxiety occurred in pregnant women before the delivery process. Anxiety increased 1.7 times delivery with Sectio Caesarea. One of the non-pharmacological treatments that can overcome the anxiety of pregnant women is diaphragmatic breathing exercises. The purpose of the study was to determine the effectiveness of diaphragmatic breathing exercises on the anxiety of third trimester pregnant women in Palembang City. Methods: the type of research used is pre-experimental with one group pre-test post-test design. The research sample was 38 respondents in the third trimester of pregnancy. The statistical test used to be the Wilcoxon test with a 95% confidence level. Results: The analysis showed that the anxiety level of pregnant women in the third trimester decreased after doing the Diaphragm Breathing Exercise. The results of the Wilcoxon statistical test showed that there was an effect of the intervention of Diaphragm Breathing Exercise on the anxiety of pregnant women in the third trimester (p-value 0.001 0.05). Conclusion: Diaphragm Breathing Exercises can reduce the anxiety level of pregnant women in the third trimester.